Comparative Study of the Strength Properties of the Concrete with Partial Replacement of the Coarse Aggregate with Pumice and Over Burnt Bricks (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is the universally accepted  material for its adverse properties with high usage of the  concrete for all type of the works in the world, it leads to  depletion of natural resources like river sand, and granite.  Which are the components of the concrete as fine  aggregate and coarse aggregate in this project M30 grade  concrete is taken in which 10%,20%&30% of coarse  aggregate is replaced with over burnt bricks and  10%,20%and 30% of coarse aggregate replaced with  pumice by volume. And the compressive, flexural and  split tensile strength properties at 7,28& 56 days and the  unit weights of the concrete compared. In order to safe  guard the natural resources, alternate material like over  burnt bricks, pumice considered in the present project.
Keywords: Partial Replacement; Coarse Aggregate; Pumice; Over Burnt Bricks